From Goldman-archive, nr.XXI. Text on the back by Senya Fléchine, dated; Paris, August 27, 1925. Mollie Steimer: in the middle (1925)
From Goldman-archive, nr.XXI. Text on the back by Senya Fléchine, dated; Paris, August 27, 1925. Mollie Steimer: in the middle.